The Influence of The STEM Learning Model on Improving Students' Scientific Literacy and Numeracy Skills on Reaction Rate Material - Manalu, Santa M.; Sugiharti, Gulmah (Universitas Tadulako, 2025)
This study was conducted to determine whether the STEM learning model has a significant effect on students' scientific literacy and numeracy skills at the rate of material speed. The target population was grade XI students of SMA Negeri 3 Medan (consisting of 9 classes), and two classes were selected as samples through purposive sampling techniques. The type of research used was quasi-experimental (pseudo-research), with a Control Group Pretest-Posttest Design. The data collection instrument was a multiple-choice test (20 questions) designed to measure scientific literacy and numeracy, and has been tested for validity and reliability. Data analysis employed a one-tailed t-test (right-tailed) with a significance level of 0.05. The results of the statistical analysis showed that the t-count value (7.367) was greater than the t-table value (1.688), leading to the rejection of the null hypothesis (H0) and the acceptance of the alternative hypothesis (Ha). In conclusion, the STEM learning model has a significant impact on enhancing students' scientific literacy and numeracy skills in the context of reaction rates.